Responsibilites of Instrumental Witnesses In The Preparation of Notarial Deeds Containing Defects - Ius Budiasto, Luthfi; Sentot Sudarwanto, Albertus; Purwadi, Hari (CV. Inara, 2025)
A notary deed serves as an authentic piece of evidence in a legal relationship, which requires the presence of not only a notary but also an instrumental witness. The existence of instrumental witnesses is a condition for the validity of a deed, because a deed without instrumental witnesses will lose its authenticity. However, when a deed contains formal or material defects, questions arise as to the extent of the responsibility imposed on the witnesses. This study uses normative legal research methods with a statutory approach, examining the Law on Notary Positions (UUJN), the Civil Code, and relevant doctrines. This study aims to analyze the legal responsibility of instrumental witnesses in making notary deeds containing defects. This research is a normative legal research with a legislative approach. The analysis was carried out using the theory of legal responsibility and the theory of legal protection as the basis for argument. The results of the study show that the responsibilities of instrumental witnesses should be limited to formal aspects, such as attendance and deed signing. Therefore, a renewal of the notarial law is needed that explicitly regulates the limits of responsibility.